2022
DOI: 10.1111/bjd.21051
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of the decreasing trend in tumour thickness to the 2010s increase in net survival from cutaneous malignant melanoma in Italy: a population‐based investigation*

Abstract: The data that support the findings of this study are available from the Italian Association of Cancer Registries (AIRTUM). Restrictions apply to the availability of these data, which were used under license for this study. Data are available from the corresponding author with the permission of the Italian Association of Cancer Registries (AIR-TUM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 59 publications
0
19
1
Order By: Relevance
“…Indeed, a decreasing trend in median tumor thickness over the years (2003–2017) was recently recorded in a registry-based study involving a significant proportion of the Italian population. This trend was paralleled by an increase in 5-year net survival rates, which, however, was only in part attributable to the former, according to the authors [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a decreasing trend in median tumor thickness over the years (2003–2017) was recently recorded in a registry-based study involving a significant proportion of the Italian population. This trend was paralleled by an increase in 5-year net survival rates, which, however, was only in part attributable to the former, according to the authors [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In two previously published articles, we have shown that the upward incidence trend is still ongoing for both sexes (despite a risk decrease being observed in the most recent birth cohorts) 31 and that the rates of thin CMM are rising more steeply. 32 This has provided the rationale for a third round of analysis aimed at exploring the ecological association between the trends in annual dermatologic office visit rates, skin biopsy rates, incidence rates of in situ and early invasive CMM, and CMM mortality rates in a large administrative region of the north of the country over the last two decades. The results are reported herein.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings of Zamagni et al ., 1 one might raise the question of whether there is a place for costly melanoma screening programmes in order to find early‐phase thin melanomas and, consequently, to reduce mortality 4 . However, the investigators also report that the decrease in tumour thickness among male patients explains largely the survival improvement in patients diagnosed in 2008–2012 compared with those in 2003–2007, but not with those in 2013–2017 1 . In addition, in the German melanoma screening programme (SCREEN) in Schleswig‐Holstein in 2003–2004, total body examination in 360 288 individuals led to an almost 50% reduction in mortality as reported in 2012 9 .…”
mentioning
confidence: 99%
“…In this issue of the BJD , Zamagni et al 1 . present their findings of an increase in net survival from cutaneous malignant melanoma (CMM) in Italy (2003–2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation